Implementasi Peraturan Pemerintah Nomor 57 Tahun 2016 Tentang Perlindungan dan Pengelolaan Ekosistem Gambut di Provinsi Riau - Febrianda, Lis; Santoso, Arianto (Universitas Ekasakti, 2023)
The expansion of peat land use is increasing rapidly in several provinces that have large peatlands, including Riau Province. Base on Government Regulation Number 57 of 2016 concerning the Protection and Management of Peat Ecosystem Article 1 paragraph (1) explains that the protection and management of the peat ecosystem is a systematic and integrated effort carried out to conserve the function of the peat ecosystem and prevent demage to the peat ecosystem which include planning, controlling, maintenance, supervision and law enforcement. Formulation of the problem (1) how is the protection and management of peatlands in Riau Province ? (2) what are the constraints faced ? (3) how are the effort carried out ? This study used a socio-legal approach. Data used include primary and secondary data. Data collected through document studies and in-depth interviews. Descriptive qualitative data analysis technique.